Eosinophilic gastrointestinal disorders in patients with inborn errors of immunity: Data from the USIDNET registry - Tran, Paulina; Gober, Laura; Garabedian, Elizabeth K.; Fuleihan, Ramsay L.; Puck, Jennifer M.; Sullivan, Kathleen E.; Spergel, Jonathan M.; Ruffner, Melanie A. (Frontiers in Immunology, 2022)
Rationale: Eosinophilic gastrointestinal disorders (EGID), including eosinophilic esophagitis (EoE), are inflammatory disorders of the gastrointestinal mucosa mediated by complex immune mechanisms. Although there have been initial reports of EGID in patients with inborn errors of immunity (IEI), little is known about the presentation of EGID in immunodeficient individuals. Methods: We queried the U.S. Immunodeficiency Network (USIDNET) for patient records including the terms eosinophilic esophagitis, gastritis, enteritis, or colitis. We analyzed 74 patient records from the database, including diagnoses, demographics, infectious history, laboratory findings, genetic studies, therapeutic interventions, and clinical outcomes. Results: We examined 74 patient records. A total of 61 patients had isolated EoE, and 13 had distal gastrointestinal involvement consistent with EGID. The most common IEI were common variable immunodeficiency (43.2%), some form of combined immunodeficiency (21.6%), chronic granulomatous disease (8.1%), hyper-IgE syndrome (6.8%), and autoimmune lymphoproliferative syndrome (6.8%). The median age at presentation with IEI was 0.5 years (IQR 1.725, max 39 years) and 56.76% were male. Approximately 20% of the patients in the cohort received a hematopoietic stem cell transplantation for treatment of IEI, but the timing of the HSCT in relationship to the EGID diagnosis was unknown. Conclusions: Here, we report EGID in a diverse cohort of IEI patients, suggesting that both non-EoE EGID and EoE can be seen as comorbid conditions with a variety of IEI. Our data suggests that EGID may be more common in patients with IEI than would be expected based on estimates of EGID in the general population.